SISTEM PENDUKUNG KEPUTUSAN PRIORITAS PESERTA PERTUKARAN MAHASISWA MENGGUNAKAN METODE WASPAS - Alam, Dewi Pathimah; Juledi, Angga Putra; Sihombing, Volvo (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
This study aims to develop a Decision Support System (DSS) based on the WASPAS (Weighted Aggregated Sum Product Assessment) method to assist Labuhan Batu University in selecting the best students to participate in the student exchange program. Manual selection which is often subjective and prone to bias is a problem that needs to be overcome. The WASPAS method was chosen because of its ability to combine weighted addition and weighted multiplication, resulting in a more comprehensive and objective evaluation. This study includes the stages of problem identification, student data collection, determination of selection criteria, and data processing using the WASPAS method. The criteria used include English language skills, leadership, knowledge, GPA, and achievement. The results of data processing using the method obtained an alternative with the Highest Value, namely A7 with a final result of 122.86582. The results of the study showed that the application of the WASPAS method resulted in a more transparent and objective evaluation compared to the manual selection method. By using this system, it is hoped that the selection process for student exchange program participants will be more efficient and on target.